JOB SATISFACTION AND INTENTION TO QUIT OF EMPLOYEES IN NON- GOVERNMENTAL ORGANISATIONS IN SWAZILAND - Msibi, W.N (Vaal University of Technology, 2017)
The main purpose of this study was to identify and describe the factors contributing to job satisfaction among employees of non-governmental organisations (NGOs) in Swaziland and to understand the drivers leading employees to think of quitting. Non-governmental organisations are institutions that provide employment opportunities in addition to the private sector and government institutions. The success of NGOs is determined by the availability and commitment of efficient and effective human resources. However, currently, most NGOs are highly affected by staff turnover and, therefore, the quality of the service they provide to the beneficiaries is affected and the financial and non-financial costs of filling vacant posts is significantly increased. To investigate this, a quantitative study was conducted using a structured questionnaire. A total of 300 employees working in NGOs throughout Swaziland were invited to complete the questionnaire and 197 useable responses were collected. The reliability (Cronbach’s Alpha) and construct validity (factor analysis) of the questionnaire were determined. This questionnaire was found to be reliable and valid. The statistical results obtained in this study showed that both forms of job satisfaction (intrinsic and extrinsic) have an inverse relationship with employees’ intentions to quit and that intrinsic job satisfaction was found to have a stronger influence on intention to quit.